DE-IDENTIFICATION AND ANONYMIZATION: LEGAL AND TECHNICAL APPROACHES (TSUL LEGAL REPORT, 2026)
This study analyzes legal and technical approaches to data de-identification and anonymization, motivated by the need to develop balanced standards that preserve privacy without stifling beneficial data uses. Doctrinal and technical literature review methods examine provisions in major data protection laws worldwide, including the EU’s GDPR, US HIPAA, and emerging frameworks in China, India, and Uzbekistan, alongside mathematical models like differential privacy and k-anonymity. The legal analysis reveals common themes like flexible research exemptions for anonymized data and calibrating standards based on sensitivity, but also gaps such as ambiguities around pseudonymization. The technical review highlights the strengths and weaknesses of encryption, perturbation, generalization, and federation techniques, emphasizing the need to complement mathematical methods with governance controls. Key findings include the importance of allowing contextual optimization, providing detailed regulatory guidance, and addressing re-identification incentives. Recommendations are provided for advancing Uzbekistan’s data protection laws and practices based on international experiences, such as enabling public oversight, conducting localized impact assessments, and promoting privacy-enhancing technologies. The study concludes that to anonymize data in a way that enables research while also protecting people’s rights, we need a comprehensive approach that includes laws, organizational rules, technical safeguards, ethical decision-making, and public input. All of these parts working together is important for successful data anonymization.